Changes in the population of structure of the spectacled caiman, Caiman crocodilus (Crocodilia: Caimanidae) and its possible relation with climate change, in Caño Negro, Costa Rica (UNED Research Journal, 2017)
The spectacled caiman, Caiman crocodilus, is ecologically and economicaly important in some areas of Latin America. In Costa Rica it is not abundant and there is a need for population data. I studied it in Caño Negro National Wildlife Refuge, Costa Rica, through the collection and comparison of previous studies and the incorporation of recent information. I made night boat trips with a 2 million lumen lamp (400m spectrum) and manually captured individuals under 60cm long. For larger sizes or animals located in areas of difficult access, I used Thompson ties and 2m long poles with an inserted rope, and captured 180 caiman. Most were sub-adults and there were 1:12 females per male, unusually high for the species and possibly caused by environmental conditions. The efects of global warming could disrupt the sex ratio and reproductive structure of spectacled caimans.
Keywords: Caymans; conservation; crocodylians; wildlife manage¬ment; sex ratio.